2009
DOI: 10.1007/s11764-009-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of occupational upper extremity use in breast cancer related upper extremity lymphedema

Abstract: Group-3 had the worst BCRL clinical stage and grade status and other breast cancer treatment related morbities. Occupations that require greater use of the upper extremities. At present there is a need for closer monitoring of patients with more severe BCRL. Potential exacerbating and maintaining factors of functional limitations and pain need to considered so that clinical management addresses these in relation to daily use of the affected UE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“…However Tahan et al, 2010 found that the patient's occupation is not only an autonomous risk factor for BRCL but also a valuable indicator for further BCRL related symptoms (shoulder restriction and arm pain) and therapy needs (physiotherapy and pain medicine needs).Regarding our results, this could be explained by the variable pain threshold among our studied group although the pain intensity was not high enough in group III.…”
Section: Discussioncontrasting
confidence: 61%
“…However Tahan et al, 2010 found that the patient's occupation is not only an autonomous risk factor for BRCL but also a valuable indicator for further BCRL related symptoms (shoulder restriction and arm pain) and therapy needs (physiotherapy and pain medicine needs).Regarding our results, this could be explained by the variable pain threshold among our studied group although the pain intensity was not high enough in group III.…”
Section: Discussioncontrasting
confidence: 61%
“…Also, prolonged use of the affected limb was found to increase the severity of LE. 19 In our study, 19 participants (50.0%) were housewives, 8 (21.1%) working actively and 11 (28.9%) not working actively. LE was found to be more common in housewives who, in their daily work, often use extremities and engage in heavy lifting.…”
Section: Upper Extremity Functions In Patients With Lymphedemamentioning
confidence: 49%
“…17,18 In some studies, more frequent and severe LE was observed after heavy work or excessive use of an affected extremity. 19 Tahan et al studied 55 patients, with an occupation that required vigorous use of the upper limbs, who had a high grade of BCRL after breast cancer surgery. In that study, Group 1 included patients who worked continuously less than 30 minutes at a time and equal to or less than 8 hours per day.…”
Section: Upper Extremity Functions In Patients With Lymphedemamentioning
confidence: 99%
“…Although there is no unique sign or criteria for defining LE, the diagnosis is usually made clinically by thorough evaluation and physical examination (2,3,10). Family history is important in the diagnosis of primary LE.…”
Section: Diagnosismentioning
confidence: 99%